2004
DOI: 10.1007/s11663-004-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical simulation and physical modeling of unsteady fluid flows in a water model of a slab mold

Abstract: Fluid flow of water in a model of a slab caster has been simulated using the large eddy simulation (LES) computational approach, and the simulated results are compared with experimental measurements performed using digital particle image velocimetry (DPIV) techniques. Simulation results agree acceptably well with the experimental measurements of instantaneous velocity fields. Flow patterns change with time as a consequence of the vertical oscillation of the jet core. These oscillations are originated by the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 17 publications
3
46
1
Order By: Relevance
“…Mathematical simulations and physical experiments have been developed and applied to study the flow patterns and the velocity fields in the mold region. [6][7][8] Banderas et al 9) characterized the periodical behavior of turbulent flows using the large eddy simulation (LES) computational approach, which compared with the Digital Particle Image Velocimetry (DPIV) measurement. A similar model by Lopez et al 10) included the effects of casting speed on fluid-flow structure, meniscus topography and kinetic energy distri- bution.…”
Section: Transient Thermo-fluid and Solidification Behaviors In Contimentioning
confidence: 99%
“…Mathematical simulations and physical experiments have been developed and applied to study the flow patterns and the velocity fields in the mold region. [6][7][8] Banderas et al 9) characterized the periodical behavior of turbulent flows using the large eddy simulation (LES) computational approach, which compared with the Digital Particle Image Velocimetry (DPIV) measurement. A similar model by Lopez et al 10) included the effects of casting speed on fluid-flow structure, meniscus topography and kinetic energy distri- bution.…”
Section: Transient Thermo-fluid and Solidification Behaviors In Contimentioning
confidence: 99%
“…The cassette filter function 23) was used in this work, G(x, x′) can be expressed as: (2) where V = ΔxΔyΔz is the volume of a computational cell.…”
Section: Governing Equationmentioning
confidence: 99%
“…2, obtained from the k-ε model, the predicted flow pattern inside the present calculation mold was symmetric and stable, failure to explain the asymmetrical and oscillating fluid flow inside the mold. In recent studies, 8,10,22,23) the large eddy simulation (LES) has been successfully applied to obtain the transient asymmetrical flow inside the mold. Yuan et al 22) combined LES and particle image velocimetry (PIV) measurements in a scaled water model, finding good agreement between both types of data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honeyands pointed out that the interaction between the confined jets and the recirculating fluid eddies could be a critical factor responsible for the oscillation in the thin slab flow system. Ramos-Banderas et al 6) studied the fluid flow of water in the slab mould using Digital Particle Image Velocimetry (DPIV) and found that the asymmetry of fluid flows and the flow pattern changed with time as a consequence of the vertical oscillation of the jet core. The jet angle and its impinging position on the mould narrow face varied with time corroborating the oscillatory motion of the entry jet.…”
Section: Introductionmentioning
confidence: 99%